Mity a rzeczywistość. Język polski w oczach cudzoziemców (na przykładzie uczestników kursu letniego NAWA 2024 w CJKP UMCS) .......... 225 - Dunin-Dudkowska, Anna; Małyska, Agata (70 lat polonistyki Pekińskiego Uniwersytetu Języków Obcych: Dziedzictwo, rozwój, innowacje, 2025)
MYTHS VS. REALITY. POLISH IN THE EYES OF FOREIGNERS (ON THE EXAMPLE OF THE PARTICIPANTS OF THE NAWA SUMMER COURSE 2024 AT CJKP UMCS IN LUBLIN)The purpose of this article is to confront the myths about the level of difficulty of the Polish language functioning among Poles and foreigners with the opinions of the students of the NAWA 2024 Summer Course, held at the Center of Polish Language and Culture for Polish People from Abroad and Foreigners of the Maria Curie-Sklodowska University in Lublin. The characteristics of the Polish language system and its subsystems: pronunciation, inflection, vocabulary, syntax and vocabulary were presented. Quantitative and qualitative research was used in the study, which made it possible to show the analyzed phenomenon more fully. The survey included 88 students from 36 countries, including 31 Slavs and 57 Non-Slavs. The results of the study reveal that the Polish language, in the eyes of the learners, shows an average level of difficulty. Slavs were more likely to respond that Polish was moderately difficult or easy, while Non-Slavs considered it moderately difficult or difficult. Perceptions of Polish as easy also increased as language proficiency increased, i.e. from B1/B2 and B2 levels. Learners said that, like other languages, Polish contains easy and difficult elements, and that the process of learning the language is long and requires patience. According to the respondents, the most difficult issues are inflection and pronunciation, while the easiest ones included vocabulary and syntax.